Health, Quality of Life and Sport Rehabilitation - Taiar, Redha; Bernardo-Filho, Mario; Rodrigues Lacerda, Ana Cristina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The aim of this Special Issue is to specify relevant principles of mathematics and mechanics in order to explore and understand biological problems. We summarize the most important parameters that influence human performance and that are related to the health sciences for all age groups, throughout their lives. We present papers that aim to introduce the latest research in the fields of health, quality-of-life improvement, and sport rehabilitation and that summarize their recommendations for best practice. The aim for this Special Issue is, therefore, to effectively combine and coordinate research and results in order to understand and improve human movement in medicine, sports, and at work.